(untitled) (Damascus University Journal of agriculture sciences, 2026)
This study aims to evaluate the performance of the Aquacrop model to simulate the productivity (grain yield - biomass) of some wheat cultivars grown in the city of Damascus rural - the town of Karhta, (irrigated) Cham9 – Cham7 - Doma1 (durum) and Cham4– Bohoth8– Cham10 (aestivum) with a seeding rate of (200) kg.hectare-1, cultivation was carried out for two growing seasons 2014-2015 and 2015-2016, the data of the 2014-2015 agricultural season was used to calibrate the model, the performance of the model was evaluated using the measures of variation, the results showed good results for both grain yield and biomass, the MBE and MAE achieved values ​​that ranged between (0.05 - 0.31), and the values ​​of the RMSE were good, ranging between (0.06 - 0.32), and the agreement was from good to very good, according to the Wilmott index by (99%), and the NRMSE value ranging between (1- 2%). The data of the 2015-2016 growing season was used to validation the model ability to simulate, the MBE and MAE achieved good values ​​that ranged between (0.02 - 0.04), and the RMSE values ​​were good, ranging between (0.03 - 0.19), and the agreement was from good to good according to the Wilmot index by (99%), and the NRMSE value ​​ (1%), which indicates the accuracy of the Aquacrop model to simulating the growth of wheat varieties grown in the study area, and the possibility of using it in studying the impact of expected climate changes on the productivity of Wheat varieties grown in the region.